Inflammation‐nutritional markers of peripheral blood could predict survival in advanced non‐small‐cell lung cancer patients treated with PD‐1 inhibitors. Issue 21 (28th September 2021) - Pu, Dan; Xu, Qian; Zhou, Lai‐Yan; Zhou, Yu‐Wen; Liu, Ji‐Yan; Ma, Xue‐Lei
Abstract: Background: Inflammation‐nutritional markers of peripheral blood are easily assessed and can predict survival. The aim of this study was to investigate the association between inflammation‐nutritional parameters and survival of anti‐programmed death‐1 (PD‐1) therapy in non‐small‐cell lung cancer (NSCLC) patients. Methods: We performed a retrospective study from March 2017 to April 2020 in advanced NSCLC patients treated with PD‐1 inhibitors. Univariable and multivariable analyses were conducted to evaluate the relationship between peripheral blood parameters (absolute lymphocyte count [ALC], absolute neutrophil count [ANC], absolute monocyte count [AMC], absolute eosinocyte count [AEC], lactic dehydrogenase [LDH], plasma‐albumin [ALB], neutrophil/lymphocyte ratio [NLR], and platelet/lymphocyte ratio [PLR]) measured before therapy initiation and prognosis. Results: Among 184 evaluable patients, 134 (72.8%) were male and the median age was 58 years (range 33–87) with 31 (16.8%) ≥70 years. An elevated ANC (≥7500/ul), NLR (≥5), and PLR (≥200) was significantly associated with worse objective response rate (ORR), progression‐free survival (PFS), and overall survival (OS), while increased ALC (≥1000/ul) and ALB (≥3.5 g/dl) could significantly improve survival in terms of ORR, PFS, and OS. In multivariate analyses, higher AEC (≥150/ul) and AMC (≥650/ul) could significantly decrease the risk of death (hazard ratio [HR] 0.363, 95% confidence interval [CI] 0.141–0.931, p = 0.035; HR 0.370, 95% CI 0.203–0.675, p = 0.001). A higher NLR and PLR, and lower ALB were independent predictors of poor prognosis for OS (HR 1.964, 95% CI 1.027–3.755, p = 0.041; HR 4.255, 95% CI 2.364–7.658, p = 0.000; HR 1.962, 95% CI 1.213–3.174, p = 0.006, respectively). Conclusion: Our research illustrated that pretreatment AEC, AMC, ALB, NLR, and PLR are independent predictors for survival in advanced NSCLC patients treated with PD‐1 inhibitors. Abstract : Pretreatment absolute eosinocyte count, absolute monocyte count, plasma‐albumin, neutrophil/lymphocyte ratio, and platelet/lymphocyte ratio were independent predictors of programmed death‐1 (PD‐1) inhibitors. These markers could help clinicians identify subpopulations who were more likely to benefit from anti‐PD‐1 therapy.